In vitro Activity of a New Fourth-Generation Cephalosporin, Cefoselis, Against Clinically Important Bacterial Pathogens in China - Cheng, Jing-Wei; Su, Jian-Rong; Xiao, Meng; Yu, Shu-Ying; Zhang, Ge; Zhang, Jing-Jia; Yang, Yang; Duan, Si-Meng; Kudinha, Timothy; Yang, Qi-Wen; Xu, Ying-Chun (Frontiers in Microbiology, 2020)
The objective of this study was to systematically evaluate the in vitro activity of cefoselis and other comparators against common bacterial pathogens collected from 18 hospitals across China. Minimum inhibitory concentrations (MICs) were determined by the broth microdilution method following Clinical and Laboratory Standards Institute (CLSI) guidelines. Cefoselis showed poor activity against extended-spectrum β-lactamase (ESBL)-producing Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis, with susceptibility rates of < 10% each, while the susceptibility rates of this antibiotic against non-ESBL-producing strains of these organisms were 100%, 94.3%, and 97.0%, respectively. Cefoselis exhibited susceptibility rates of 56.7–83.3% against other tested Enterobacteriaceae isolates. For Acinetobacter baumannii and Pseudomonas aeruginosa isolates, the susceptibility rates to cefoselis were 18.7% and 73.3%, respectively. All methicillin-resistant Staphylococcus aureus (MRSA) strains were resistant to cefoselis, while all methicillin-sensitive S. aureus (MSSA) strains were susceptible to this antibiotic. In conclusion, cefoselis showed good activity against non-ESBL-producing E. coli, K. pneumoniae, and P. mirabilis, MSSA, and was also potent against Enterobacteriaceae, P. aeruginosa, and Streptococcus.